Slough house eaudiobook - Herron, Mick (Slough House, 2021)
At Slough House—MI5's London depository for demoted spies—Brexit has taken a toll. The "slow horses" have been pushed further into the cold, Slough House has been erased from official records, and its members are dying in unusual circumstances, at an unusual clip. No wonder Jackson Lamb's crew is feeling paranoid. But are they actually targets? With a new populist movement taking hold of London's streets and the old order ensuring that everything's for sale to the highest bidder, the world's a dangerous place for those deemed surplus. Jackson Lamb and the slow horses are in a fight for their lives as they navigate dizzying layers of lies, power, and death. In his best and most ambitious novel yet, Mick Herron, "the le Carré of the future" (BBC), offers an unsparing look at the corrupt web of media, global finance, spycraft, and politics that power our modern world.